2017
DOI: 10.4025/actascitechnol.v39i2.29370
|View full text |Cite
|
Sign up to set email alerts
|

<b>Optimization of lactic fermentation for extraction of chitin from freshwater shrimp waste

Abstract: ABSTRACT. Freshwater shrimp shells from the shrimp farming activity in tanks, were processed for biological extraction of chitin, by fermentation with Lactobacillus plantarum isolated from meat products, offering an advantageous demineralization and deproteination of the residue, replacing the chemically. Deproteination was obtained approximately 99% and demineralization of up to 87% using batch fermentations with a maximum of 72 hours and the use of simple strategies such as pH adjustment and reinoculation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…The experimental mean composition of shrimp waste and the calculated feed for simulation of the plant process are given in Table 1. The protein, mineral, chitin and pigment contents depend markedly on nutritional conditions; the results obtained in this study are in the range reported for this shrimp species ( 33 ). The astaxanthin content was slightly higher, possibly due to the supplementation of shrimp feed with carotenoids ( 34 ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The experimental mean composition of shrimp waste and the calculated feed for simulation of the plant process are given in Table 1. The protein, mineral, chitin and pigment contents depend markedly on nutritional conditions; the results obtained in this study are in the range reported for this shrimp species ( 33 ). The astaxanthin content was slightly higher, possibly due to the supplementation of shrimp feed with carotenoids ( 34 ).…”
Section: Resultssupporting
confidence: 80%
“…The strain L. plantarum has been widely explored for fermentation of chitinous waste, allowing to reach demineralization and deproteinization values higher than 80% ( 8 , 33 , 35 , 36 ). Additionally, the use of co-cultures of microorganisms has been reported as a feasible alternative to obtain demineralization and deproteinization values higher than 90% in less time, increasing the efficiency of the process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported that DP and DM takes altogether between 2 to 7 days (Sorokulova et al 2009;Aytekin & Elibol 2010;Khorrami et al 2012;Zhang et al 2012;Mao et al 2013;Ghorbel-Bellaaj et al 2013;Hajji et al 2015;Sedaghat et al 2015;Francisco et al 2015;Zhang et al 2016;Rawia et al 2016;Sedaghat et al 2017;Chakravarty et al 2018;Doan et al 2019). Some other authors have reported processing time between 24 to 254 hours (Hoffmann et al 2010;Prameela et al 2010;Wahyuntari et al 2011;Pacheco et al 2011;Duan et al 2012;Flores-Albino et al 2012;Mao et al 2013;Junianto et al 2013;Liu et al 2014;Pachapur et al 2015;Mhamdi et al 2017;Aranday-Garcia et al 2017;Neves et al 2017;Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Demineralization ( ria (Castro et al 2018;Chakravarty et al 2018;Aranday-García et al 2017;Neves et al 2017;Zhang et al 2016;Francisco et al 2015;Junianto et al 2013;Zhang et al 2012;Flores-Albino et al 2012;Khorrami et al 2012;Duan et al 2012;Wahyuntari et al 2011;Pacheco et al 2011;Aytekin & Elibol 2010).…”
Section: Deproteinization (Dp)mentioning
confidence: 99%